Pengaruh Pemberian Pisang Ambon Terhadap Penurunan Tingkat Kelelahan Kerja Pada Pekerja Industri Gamelan Desa Wirun - Femy Rahmawati; Maria Paskanita Widjanarti; Reny Wijayanti (Sekolah Vokasi, Universitas Sebelas Maret, 2026)
Work fatigue is a critical occupational health issue that leads to decreased productivity and high absenteeism rates. This study aims to analyze the effect of occupational nutritional intervention through the administration of Ambon bananas on the level of work fatigue among gamelan craftsmen in Wirun Village. A quasi-experimental design with a one-group pre-test and post-test approach was employed. A total of 30 workers were selected using the total sampling technique. The respondents' characteristics revealed a strong positive correlation between age (r = 0.698) as well as working tenure (r = 0.601) and the level of work fatigue. The intervention involved administering 150 grams of Ambon bananas for three consecutive days to address the daily caloric deficit of the workers. Work fatigue was measured using a reaction timer before and after the intervention, and the data were subsequently analyzed using the Wilcoxon test.The results showed that prior to the intervention, the workers' average reaction time was 500.82 milliseconds (moderate fatigue category), which significantly decreased to 390.14 milliseconds (light fatigue category) post-intervention. The Wilcoxon statistical test confirmed a significant difference with a p-value of 0.001 (p < 0.05). Consequently, it can be concluded that administering Ambon bananas is effective in accelerating energy recovery and reducing work fatigue among informal sector industrial workers with heavy physical workloads. This study recommends the integration of nutrient-dense snacks as a follow-up occupational health intervention to maintain workers' health and occupational productivity.